Utilization of urea as a nitrogen source for ethanol production from oil palm trunk using simultaneous saccharification and fermentation - Tareen, Afrasiab Khan; Danbamrongtrakool, Noppawan; Sultan, Imrana Niaz; Laemsak, Nicom; Sirisansaneeyakul, Sarote; Vanichsriratana, Wirat; Parakulsuksatid, Pramuk (Agriculture and Natural Resources, 2021)
The utilization of urea as a low cost nitrogen source to replace yeast extract and peptone was investigated for ethanol production using yeast Saccharomyces cerevisiae SC90 at 40°C. The effect of urea concentration (1 g/L, 2 g/L, 4 g/L and 7 g/L) was determined for ethanol production in medium consisting of 220 g/L glucose, 2 g/L KH2PO4 and 5 g/L MgSO4. The optimum urea concentration of 1 g/L produced the maximum mean (± SD) ethanol concentration of 70.53 ± 5.81 g/L. The optimized urea concentration and mixtures of yeast extract and peptone (YP) were compared for ethanol production from alkaline-extracted oil palm trunk fibers using simultaneous saccharification and fermentation (SSF). The maximum ethanol concentration, productivity, yield and theoretical ethanol yield attained with urea were 37.00 ± 0.18 g/L, 0.51 ± 0.06 g/L/hr, 0.414 ± 0.02 g/g and 81.24 ± 0.39%, respectively which were comparatively lower than those obtained when YP was used as a nitrogen source for which the ethanol concentration, ethanol productivity and theoretical ethanol yield were lowered by 14.23%, 16.70%, and 16.56%, respectively. Conversely, using urea concentration of 1 g/L as a nitrogen source could replace the YP medium for ethanol fermentation using SSF. The results showed that ethanol production using urea as a nitrogen source was a better alternative to reduce the production medium cost on an industrial scale.